Microsoft Visual C# 2010 step by step - Sharp, John, 1964- (Microsoft Press ; Dreamtech, 2010)
Your hands-on, step-by-step guide to the fundamentals of Visual C# development. This tutorial provides practical, learn-by-doing exercises for mastering C# language features and creating working applications and components for Windows-- back cover.